2017
DOI: 10.1007/s11605-016-3223-y
|View full text |Cite
|
Sign up to set email alerts
|

The Sooner, the Better? The Importance of Optimal Timing of Cholecystectomy in Acute Cholecystitis: Data from the National Swedish Registry for Gallstone Surgery, GallRiks

Abstract: Up-front cholecystectomy is the recommended therapy for acute cholecystitis (AC). However, the scientific basis for the definition of the optimal timing for surgery is scarce. The aim of this study was to analyze how the timing of surgery, after the admission to hospital for AC, affects the intra- and postoperative outcomes. Within the national Swedish Registry for Gallstone Surgery and Endoscopic Retrograde Cholangiopancreatography (GallRiks), all patients undergoing cholecystectomy for acute cholecystitis be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 25 publications
3
46
0
6
Order By: Relevance
“…[4,5] In a recent large Swedish series by Blohm et al, concluded early laparoscopic cholecystectomy for acute cholecystitis offers an advantage in the length of hospital stay without increasing the morbidity or mortality with caption 'the sooner, the better'. [6] Similarly in our study, complication rates and operating difficulties were lesser in patients who were operated in the initial period and patients on long waiting period suffered relapse of symptoms and required readmissions. Our study also concludes that early intervention reduces complications and length of hospital stay.…”
Section: Discussionsupporting
confidence: 78%
“…[4,5] In a recent large Swedish series by Blohm et al, concluded early laparoscopic cholecystectomy for acute cholecystitis offers an advantage in the length of hospital stay without increasing the morbidity or mortality with caption 'the sooner, the better'. [6] Similarly in our study, complication rates and operating difficulties were lesser in patients who were operated in the initial period and patients on long waiting period suffered relapse of symptoms and required readmissions. Our study also concludes that early intervention reduces complications and length of hospital stay.…”
Section: Discussionsupporting
confidence: 78%
“…Efforts to improve safety in LC have greatly increased the body of knowledge regarding all factors relevant to cholecystectomy. These include timing of the procedure and patient selection [19][20][21][22] as well as training and assessment of surgeons performing LC [23]. Endeavors to increase safety of the procedure resulted in optimized intraoperative processes, such as photographic documentation [24] of the 'critical view of safety' (CVS), first described by Strasberg and colleagues almost 20 years ago [25].…”
Section: Prevention Of Bile Duct Injuriesmentioning
confidence: 99%
“…Blohm in sodelavci so analizirali podatke iz švedskega nacionalnega registra pri 87.108 bolnikih, ki so bili operirani zaradi akutnega holecistitisa (30). Osredinili so se na zaplete ob in po operaciji.…”
Section: Izsledki Kliničnih šTudij In Metaanalizunclassified
“…Ugotovili so, da je tveganje za zaplete po operaciji statistično značilno nižje, če so bolniki operirani znotraj štirih dni od sprejema v bolnišnico, in da je tudi manj preklopov v klasično operacijo znotraj tega časa. Pri bolnikih, ki so jih operirali v prvih štirih dneh po sprejemu v bolnišnico, so opazovali okoli 16,6 % preklopov iz laparoskopske v klasično operacijo ter 27,8 % pri bolnikih, ki so bili operirani kasneje (30). Izguba krvi med operacijo je bila pri obeh skupinah bolnikov primerljiva, več pa je bilo poškodb žolčnih vodov pri tistih bolnikih, ki so bili operirani pozno.…”
Section: Izsledki Kliničnih šTudij In Metaanalizunclassified
See 1 more Smart Citation